Research methods in intercultural communication a practical guide - Hua, Zhu 1970- (Chichester, West Sussex, [England] John Wiley & Sons, Inc., 2016)
"The focus is on the process of interaction and what the participants achieve out of the experience in terms of new values, identities and practices"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Intercultural communication -- Research; Intercultural communication -- Methodology